Histological and functional outcomes after traumatic brain injury in mice null for the erythropoietin receptor in the central nervous system - Xiong, Ye (2008)
Erythropoietin (EPO) and its receptor (EPOR), essential for erythropoiesis, are expressed in the nervous system. Recombinant human EPO treatment promotes functional outcome after traumatic brain injury (TBI) and stroke, suggesting that the endogenous EPO/EPOR system plays an important role in neuroprotection and neurorestoration. This study was designed to investigate effects of the EPOR on histological and functional outcomes after TBI. Experimental TBI was induced in adult EPOR-null and wild-type mice by controlled cortical impact. Neurological function was assessed using the modified Morris Water Maze and footfault tests. Animals were sacrificed 35 days after injury and brain sections stained for immunohistochemistry. As compared to the wild-type injured mice, EPOR-null mice did not exhibit higher susceptibility to TBI as exemplified by tissue loss in the cortex, cell loss in the dentate gyrus, impaired spatial learning, angiogenesis and cell proliferation. We observed that less cortical neurogenesis occurred and that sensorimotor function (i.e., footfault) was more impaired in the EPOR-null mice after TBI. Co-accumulation of amyloid precursor protein (axonal injury marker) and calcium was observed in the ipsilateral thalamus in both EPOR-null and wild-type mice after TBI with more calcium deposits present in the wild-type mice. This study demonstrates for the first time that EPOR null in the nervous system aggravates sensorimotor deficits, impairs cortical neurogenesis and reduces thalamic calcium precipitation after TBI.